HOUSEHOLD FINANCES, INCOME SHOCKS, AND FAMILY SEPARATION IN BRITAIN. (12th October 2015) - Bridges, Sarah; Disney, Richard
Abstract : We examine the effect of household financial indebtedness on the incidence of partnership dissolution using a large survey of families with children in Britain. We use detailed data on household finances to provide a robust statistical analysis of the relationship between indebtedness and partnership dissolution and to avoid the potential simultaneity of financial and psychological health responses that arise when using self‐reported data on the extent of household "financial problems." We examine whether the data provide any support for the "economic" models of divorce and separation developed by Gary Becker and his colleagues. ( JEL J12, D12)